Kepastian Hukum Lelang Eksekusi Objek Hak Tanggungan Berdasarkan Parate Executie - Rahmadi Indra Tektona; Moh. Ali; Anang Suindro (Jurnal Hukum dan Sosial Politik, 2023)
In general, there are laws that provide protection to banks as lenders to obtain repayment of their debts when the debtor is in default, this is stated in Article 1131 of the Civil Code which reads: "All assets of the Debtor, whether movable or immovable, whether existing ones or those that will be in the future become dependents/guarantees. Debtor's assets, both movable and immovable, both present and future will become dependents/guarantee for their debts. One of the characteristics of the UUHT is that it is easy and certain to execute, which means executing the mortgage certificate. must be carried out but can still provide legal certainty for interested parties, in this case, the auction seller, auction buyer and auctioneer. Therefore, in carrying out executions based on parate execution, it must be able to provide convenience and legal certainty for all interested parties.